Nicotianamine synthase overexpression positively modulates iron homeostasis-related genes in high iron rice - Wang, Meng; Gruissem, Wilhelm; Bhullar, Navreet K. (Frontiers in Plant Science, 2013)
Nearly one-third of the world population, mostly women and children, suffer from iron malnutrition and its consequences, such as anemia or impaired mental development. Biofortification of rice, which is a staple crop for nearly half of the world’s population, can significantly contribute in alleviating iron deficiency. NFP rice (transgenic rice expressing nicotianamine synthase, ferritin and phytase genes) has a more than six-fold increase in iron content in polished rice grains, resulting from the synergistic action of nicotianamine synthase (NAS) and ferritin transgenes. We investigated iron homeostasis in NFP plants by analyzing the expression of 28 endogenous rice genes known to be involved in the homeostasis of iron and other metals, in iron-deficient and iron-sufficient conditions. RNA was collected from different tissues (roots, flag leaves, grains) and at three developmental stages during grain filling. NFP plants showed increased sensitivity to iron-deficiency conditions and changes in the expression of endogenous genes involved in nicotianamine (NA) metabolism, in comparison to their non-transgenic siblings. Elevated transcript levels were detected in NFP plants for several iron transporters. In contrast, expression of OsYSL2, which encodes a member of Yellow Stripe-like protein family, and a transporter of the NA-Fe(II) complex was reduced in NFP plants under low iron conditions, indicating that expression of OsYSL2 is regulated by the endogenous iron status. Expression of the transgenes did not significantly affect overall iron homeostasis in NFP plants, which establishes the engineered push-pull mechanism as a suitable strategy to increase rice endosperm iron content.